Case Report: Glucocorticoid Effect Observation in a Ureteral Urothelial Cancer Patient With ICI-Associated Myocarditis and Multiple Organ Injuries - Hu, Xiajun; Wei, Yumiao; Shuai, Xinxin (Frontiers in Immunology, 2021)
Immune checkpoint inhibitor (ICI)-associated immune-related adverse events (irAEs) are becoming important safety issues worthy of attention despite the exciting therapeutic prospects. The growing development of new ICIs also brings new cases of irAEs, raising more challenges to clinicians. Cardiac injury is rare but life-threatening among diverse organ injuries, and effective interventions are critical for patients. Here, we report a novel programmed cell death protein-1 (PD-1) inhibitor tislelizumab-associated severe myocarditis and myositis accompanied by liver and kidney damage in a ureteral urothelial cancer patient, who was firstly treated by cardiologists because of cardiac symptoms. Due to the lack of experience about ICI-associated irAEs, an initial low-dose (0.5 mg/kg/day) and short-term methylprednisolone therapy was used and found to be ineffective and risky to the patient; then, steroid therapy was modulated to a higher dose (1.5 mg/kg/day) with prolonged time course, and improvement of patient symptoms and laboratory markers were observed quickly and persistently. The patient did not show adverse events under this steroid dosage. This case reports a rare tislelizumab-related myocarditis and multiple organ injuries, which provides valuable experience to cardiologists like us. Early recognition of ICI-associated myocarditis and sufficient dosage and time course of glucocorticoid therapy are critical for severe cases. High-quality clinical evidence about the precise diagnosis and therapy in ICI-associated myocarditis and other organ injuries are necessary to guide our clinical works.